Reluctant saint? A theological biography of Fletcher of Madeley by P. Streiff - K. Roy (Acta Theologica)
From text: It was said of Martyn Lloyd-Jones that whenever he felt depressed he would retreat to the eighteenth century and refresh himself with the accounts of the great Methodist preachers and revivals of the era. Surely he would have enjoyed this biography of Fletcher of Madeley, notwithstanding his different theological perspective.